STUDY ON CONSUMERS PERCEPTION AND KNOWLEDGE ON VEGETAL ORGANIC BY-PRODUCTS USED AS FUNCTIONAL INGREDIENTS - Mihaela Cristina DRAGHICI; Amalia Carmen MITELUT; Elisabeta Elena POPA; Paul Alexandru POPESCU; Vlad Ioan POPA; Andreea BARBU; Mona Elena POPA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In recent years the increase in demand and consumption of minimally processed organic products has been more and more desired because of the consumer awareness of a healthier diet, as well as the responsibility for the environment sustainability. Consumers expect a better quality for these organic products compared to conventional ones, thus referring to a lower content of pesticide residues and additives, respectively better nutritional and quality attributes. This study provides a perspective on the consumer behaviour and attitude toward organic food products enriched in value by adding nutrients resulting from the minimally processing of organic fruits and vegetables. The research is based on a survey answered by 547 respondents and which uses a questionnaire designed based on the literature and the conclusions previously obtained in an ongoing research project.